1999
DOI: 10.1002/1529-0131(199904)42:4<799::aid-anr25>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated parathyroid hormone 44-68 and osteoarticular changes in patients with genetic hemochromatosis

Abstract: Liver iron overload syndromes, especially genetic hemochromatosis, are associated with elevated circulating levels of PTH fragments containing the 44-68 region, which appears to play a role in osteoarticular changes. This increase seems to be a consequence of iron overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
12

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 24 publications
2
13
0
12
Order By: Relevance
“…Cirrhosis and liver cancer can now be prevented by early phlebotomy therapy which maintains low iron stores [2,3]. Therefore, hemochromatosis has currently become a chronic disease with functional consequences and rheumatological manifestations such as arthritis [4] or osteoporosis [5] which are now of concern for physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Cirrhosis and liver cancer can now be prevented by early phlebotomy therapy which maintains low iron stores [2,3]. Therefore, hemochromatosis has currently become a chronic disease with functional consequences and rheumatological manifestations such as arthritis [4] or osteoporosis [5] which are now of concern for physicians.…”
Section: Introductionmentioning
confidence: 99%
“…De plus, à l'heure où le traitement préventif par saignées permet de prévenir les complications vitales de la maladie, ce sont les signes fonctionnels articulaires qui diminuent la qualité de vie des patients. Les manifestations articulaires sont souvent au premier plan, retrouvées dans 64 % des cas chez des patients issus d'un centre de dépistage, non encore traités, d'âge moyen 50 ans [2]. Elles seraient inaugurales dans 20 à 37 % des cas.…”
Section: ■ Points Essentielsunclassified
“…Les atteintes articulaires de l'hémochromatose génétique sont fréquentes (64 % des cas) et volontiers révélatrices de la maladie (20 à 37 % des cas), mais elles sont négligées au moins 1 fois sur 2 [2,9]. Ceci est probablement dû au fait qu'elles ont finalement peu de spécificité sur le plan clinique.…”
Section: Manifestations Articulaires De L'hémochromatose Génétiqueunclassified
See 1 more Smart Citation
“…The strongest associations after aging are with hyperparathyroidism and hemochromatosis. Pawlotsky et al [42] recently suggested that these two diseases may be linked. They showed that patients with hemochromatosis had elevated serum levels of parathyroid hormone (PTH).…”
Section: Associated Diseasesmentioning
confidence: 99%